Dopaminergic Progenitors Derived From Epiblast Stem Cells Function Similarly to Primary VM-Derived Progenitors When Transplanted Into a Parkinson’s Disease Model - Precious, Sophie V.; Smith, Gaynor A.; Heuer, Andreas; Jaeger, Ines; Lane, Emma L.; Dunnett, Stephen B.; Li, Meng; Kelly, Claire M.; Rosser, Anne E. (Frontiers in Neuroscience, 2020)
Neural transplantation in neurodegenerative diseases such as Parkinson’s disease (PD) offers to replace cells lost during the progression of the disease process. Primary fetal ventral mesencephalon (VM), the origin of bona fide midbrain dopaminergic (DAergic) precursors, is currently the gold standard source of cells for transplantation in PD. However, the use of tissue from this source raises ethical and logistical constraints necessitating the need for alternative supplies of donor cells. The requirement of any alternative donor cell source is to have the capability to generate authentic mature DAergic neurons, which could be utilised in cell-replacement strategies. Mouse pluripotent stem cells can efficiently generate electrochemically mature midbrain DAergic precursors in vitro using a stepwise control of FGF signaling. Here, we have compared DAergic transplants derived from two progenitor cell sources in an allograft system: mouse epiblast stem cells and primary fetal mouse VM tissue. Cells were transplanted into the striatum of 6-OHDA lesioned mice pre-treated with L-DOPA. Drug-induced rotations, a number of motor tests and drug-induced abnormal involuntary movements (AIMs) were assessed. Functional improvements were demonstrated post-transplantation in some behavioural tests, with no difference in graft volume or the number of TH immuno-positive cells in the grafts of the two transplant groups. L-DOPA-induced AIMs and amphetamine-induced AIMs were observed in both transplant groups, with no differences in rate or severity between the two groups. Collectively, in this mouse-to-mouse allograft system, we report no significant differences in the functional ability between the gold standard primary VM derived and pluripotent stem cell-derived DAergic transplants.